2019
DOI: 10.1038/s41598-019-50717-9
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic and hepatoprotective properties of alkali- and enzyme-extractable polysaccharides by Dictyophora indusiata

Abstract: Hyperlipidemia, a very common disease throughout the world, usually gives rise to severe liver damages. The current experiment was to investigate the antihyperlipidemic and hepatoprotective properties of alkali- and enzyme-extractable Dictyophora indusiata polysaccharides (Al-DPS and En-DPS) on the hyperlipidemic mice. The results of animal experiment in vivo showed that treatment with Al-DPS or En-DPS could improve the excessive level of lipid profiles in serum and liver, as well as strengthen antioxidant sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In high fat-induced oxidative damage model, the water soluble polysaccharides administered in mice could abolish the increased LPO (MDA level) while increasing the antioxidant status by elevating SOD, GPx, CAT and total antioxidant capacity (T-AOC) contents/activities in the liver and kidney tissues [14,35]. Similar with this observation was the study by Wang et al that showed organoprotective (hepatoprotective) effect along with increased antioxidant status in obese and hyperlipidemic mice [48]. Other in vivo model for the demonstration of antioxidant effects was the colitis model in mice where intestinal oxidative stress as assessed by the increased MDA level and GSH depletion markers which were normalized by β-glucans [4].…”
Section: Antioxidant Effectsupporting
confidence: 55%
See 2 more Smart Citations
“…In high fat-induced oxidative damage model, the water soluble polysaccharides administered in mice could abolish the increased LPO (MDA level) while increasing the antioxidant status by elevating SOD, GPx, CAT and total antioxidant capacity (T-AOC) contents/activities in the liver and kidney tissues [14,35]. Similar with this observation was the study by Wang et al that showed organoprotective (hepatoprotective) effect along with increased antioxidant status in obese and hyperlipidemic mice [48]. Other in vivo model for the demonstration of antioxidant effects was the colitis model in mice where intestinal oxidative stress as assessed by the increased MDA level and GSH depletion markers which were normalized by β-glucans [4].…”
Section: Antioxidant Effectsupporting
confidence: 55%
“…These activities imply a wider effect of organoprotective effect primarily where oxidative stress is implicated and also in obesity-associated diseases like diabetes and cardiovascular complications. Wang et al [48] also employed the high-fat-induced obesity and hyperlipidemia model to assess the potential antidiabetic effects of D. indusiata polysaccharides obtained by enzyme assisted or alkali extraction method ( Table 2). They have demonstrated a direct glucose lowering effects under OGTT while the alteration in the serum adiponectin level and the increases in insulin and leptin were normalized.…”
Section: Antiobesity and Potential Antidiabetic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing evidence has confirmed that fungal polysaccharides and their sulfated derivatives from mushrooms show various bioactivities [19–22] . Some sulfated fungal polysaccharides, such as Pleurotus eous , Russula virescens , Ganoderma atrum , Pleurotus eryngii and Pleurotus sajor‐caju , can elevate the existing antioxidant, anticoagulant, antitumor and antibacterial activities [23–26] .…”
Section: Introductionmentioning
confidence: 99%
“…Phallus indusiatus has a cosmopolitan distribution in the tropics and subtropics, including southern Asia, Africa, Australia, and the Americas (Bandala et al, 1999). Phallus indusiatus fruiting bodies, and their polysaccharide components, have immunoregulatory (Hua et al, 2012;Liao et al, 2015), antioxidative (Nguyen et al, 2013), anti-inflammatory (Nguyen et al, 2013), antineoplastic (Deng et al, 2013), neuroprotective (Zhang et al, 2016), antihyperlipidemic, and hepatoprotective (Wang et al, 2019) activities. Phallus echinovolvatus is widely cultivated in China because of its strong resistance to high temperatures and drought and its pharmacological activity (Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%